2009
DOI: 10.1111/j.1468-1331.2009.02546.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of executive deficit following ruptured anterior communicating artery aneurysm

Abstract: This study supports that (i) cognitive executive deficits depend mostly on lateral prefrontal lesions, (ii) with locations varying according to executive process, and (iii) behavioral executive deficits are mainly due to left ventral striatum lesion in post-aneurysmal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 37 publications
2
39
0
2
Order By: Relevance
“…The ventral striatum has long been a candidate structure for addiction vulnerability given its central role in salience-processing, reward-learning, acute response to illicit drugs and alcohol, and demonstrated abnormalities in addicted populations (Koob and Volkow, 2010). The left ventral striatum also contributes to Go/No-Go performance in a manner sensitive to FHP (Heitzeg et al, 2010), consistent with findings suggesting a role for the left ventral striatum in hyperactive behaviors (Martinaud et al, 2009).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The ventral striatum has long been a candidate structure for addiction vulnerability given its central role in salience-processing, reward-learning, acute response to illicit drugs and alcohol, and demonstrated abnormalities in addicted populations (Koob and Volkow, 2010). The left ventral striatum also contributes to Go/No-Go performance in a manner sensitive to FHP (Heitzeg et al, 2010), consistent with findings suggesting a role for the left ventral striatum in hyperactive behaviors (Martinaud et al, 2009).…”
Section: Introductionsupporting
confidence: 69%
“…The ventral striatum has long been a candidate structure for addiction vulnerability given its central role in salience-processing, reward-learning, acute response to illicit drugs and alcohol, and demonstrated abnormalities in addicted populations (Koob and Volkow, 2010). The left ventral striatum also contributes to Go/No-Go performance in a manner sensitive to FHP (Heitzeg et al, 2010), consistent with findings suggesting a role for the left ventral striatum in hyperactive behaviors (Martinaud et al, 2009).To account for impulsivity's multi-factorial nature and the relevance of related constructs to addiction vulnerability, extensive out-of-scanner measures assessing impulsivity and related constructs (reward and punishment sensitivity, attention, compulsivity, risk-taking, sensationseeking) were consolidated into five factors, based on a previously published factor analysis (Meda et al, 2009). Measures of age of drinking onset and past-month alcohol consumption were explored in relation to regional FHPrelated differences in BOLD signal and impulsivity-related factors.…”
supporting
confidence: 68%
“…31,32 Third, cognitive deficits have been strongly correlated to hippocampal CA1 neuronal cell number after experimental SAH. 15 To be sure, other structural areas may also play a role, including left hemispheric lesions, 33 reductions in total gray and white matter volume 34 (in patients), and cortical neuronal cell loss (in rats). 15 In total, these data provide substantial evidence that hippocampal damage plays a key role in SAH-induced cognitive deficits, but that alterations in other brain areas also contribute.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the prevalence of executive dysfunction in aSAH survivors is very wide with estimates ranging from 3% to 76%. 10,[12][13][14][15][16][17][18][19]37 Interestingly, self-reported deficits in executive function do not appear to correlate with results from objective cognitive tests; Ravnik and colleagues 38 found that patients with aSAH reported attentional deficits most frequently, yet patients performed better on tests of attention than on tests of other cognitive domains. Discordance between self-reported cognitive deficits and results from objective cognitive tests has also been reported in other domains, like memory.…”
Section: Executive Functionmentioning
confidence: 99%
“…An MRI study by Martinaud and colleagues, 15 for instance, suggested that executive dysfunction results from focal lesions rather than diffuse damage. Martinaud and colleagues 15 showed that executive dysfunction in patients with aSAH was exclusively correlated with lesions to the left hemisphere.…”
Section: Executive Functionmentioning
confidence: 99%